Force generation capacity of knee extensor muscles in speed skaters - Kanehisa, H.; Nemoto, I.; Okuyama, H.; Ikegawa, S.; Fukunaga, T. (European Journal of Applied Physiology, 1996)
The force generation capacities during a single as well as repetitive maximal knee extensions were investigated in speed skaters in relation to the cross-sectional area (CSA) of quadriceps femoris muscles. The subjects were 15 male and 12 female speed skaters, and an age-matched untrained group (20 men and 21 women). An isokinetic dynamometer was used to determine force output at three constant velocities of 1.05, 3.14 and 5.24 rad.s-1 and to perform 50 repetitive maximal contractions at 3.14 rad.s-1. The CSA was measured by using a B-mode ultrasound technique at the midpoint of the thigh length. The isokinetic force produced at each test velocity was significantly correlated to CSA in all the subjects (r = 0.867-0.920, P < 0.05). There was no significant difference in force (F) per unit CSA (F.CSA-1) at the three test velocities between the speed skaters and untrained subjects within the same sex. In both the speed skaters and untrained subjects, the women showed significantly lower F.CSA-1 at 3.14 and 5.24 rad.s-1 than the men. The means of force output (F) of every five consecutive and all trials during the repetitive maximal bout were significantly correlated to CSA in all the subjects (r = 0.889-0.934, P < 0.05). Compared to the untrained subjects, the speed skaters showed significantly higher F for every five consecutive contractions even when calculated per unit of CSA (F.CSA-1), and had lower percentage of decline of F during a trial span between the 6th-10th and 41st-45th trials. For the untrained subjects, F.CSA-1 for every five consecutive contractions was significantly lower in the women than in the men. For the speed skaters, the men showed significantly higher F.CSA-1 than the women during a trial span from the 1st-5th trial to the 31st-35th trial, although there was no significant sex difference in the ratio on and after the 36th-40th trial. From these results, it is concluded that the speed skaters show a higher muscle performance in a repetitive maximal contraction task rather than in a single contraction compared to the untrained subjects. In addition, judging from the results for the speed skaters, the women might be less trainable than the men in the F.CSA-1 during a single contraction at a fast velocity as well as repetitive maximal contractions.